Environmental degradation and output volatility: A global perspective - Muhammad Tariq Majeed; Maria Mazhar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study examines the link between environmental indicators and output volatility unlike the previous literature that mainly emphasized the importance of carbon emissions and economic growth nexus. Output uncertainty is considered a serious global issue as it undermines economic gains and quality of life. This study scrutinizes the impact of greenhouse gas emissions on output volatility in 155 countries over the period 1971-2017. The empirical analysis is based on Pooled Ordinary Least Squares, Random and Fixed Effects Models. The empirical results confirm that carbon dioxide (CO2), nitrogen oxide (NOX), methane (CH4), and total greenhouse gas (GHG) emissions are positively contributing to amplify global output volatility. Moreover, the Principal Component Analysis (PCA) of pollutant indicators also confirms the main results. Comparatively carbon emissions are contributing more to augment output volatility. A comparative analysis also reveals that all pollutants augment output volatility more in agricultural economies. The results of Granger causality confirm the bidirectional causality between environmental degradation and output volatility providing an evidence of endogeneity problem. To address it, the system GMM estimator is used by incorporating the instruments in output volatility model and the results of system GMM are also consistent with main findings. Findings of the study imply that a promising path of sustainable growth can be achieved by adopting the alternative ways of energy resources that produce less pollutant relative to greenhouse gasses.
Keywords: 330; output volatility; environmental degradation; greenhouse gases; GDP per capita; CO2 emissions; NOX emissions; CH4 emissions